2002
DOI: 10.1021/ol0264096
|View full text |Cite
|
Sign up to set email alerts
|

2,7-Bis(1H-pyrrol-2-yl)ethynyl-1,8naphthyridine:  An Ultrasensitive Fluorescent Probe for Glucopyranoside

Abstract: [structure: see text] A push-pull conjugated molecule, 2,7-bis(1H-pyrrol-2-yl)ethynyl-1,8-naphthyridine (BPN), has been designed to bind selectively with octyl glucopyranoside (OGU). The BPN/OGU quadruple hydrogen-bonding complex adopts a rigid BPN conformation in which the proton donor (d) and acceptor (a) relays (daad) are resonantly conjugated through the ethynyl bridge, inducing pi-electron delocalization, i.e., a charge transfer effect. The excellent photophysical properties make BPN a highly sensitive pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(11 citation statements)
references
References 37 publications
0
11
0
Order By: Relevance
“…Addition of Al 3+ up to 1.3 μM to the probe makes significant 39 fold fluorescence enhancement at 431 nm within few seconds (Figure b). The resultant binding constant of the probe PTI with Al 3+ is 1.23 × 10 6 M −1 , obtained from the fluorescence titration (Figure S5, see Supporting Information) determined by non‐linear fitting analyses of the titration curves following the published reports . Detection limit has been well calculated from the linear relationship between PTI and Al 3+ as 45 nM (Figure S6, see Supporting Information).…”
Section: Resultsmentioning
confidence: 89%
“…Addition of Al 3+ up to 1.3 μM to the probe makes significant 39 fold fluorescence enhancement at 431 nm within few seconds (Figure b). The resultant binding constant of the probe PTI with Al 3+ is 1.23 × 10 6 M −1 , obtained from the fluorescence titration (Figure S5, see Supporting Information) determined by non‐linear fitting analyses of the titration curves following the published reports . Detection limit has been well calculated from the linear relationship between PTI and Al 3+ as 45 nM (Figure S6, see Supporting Information).…”
Section: Resultsmentioning
confidence: 89%
“…The corresponding association constant (K a ) of APR−Hyp complex from the fluorescence titration was determined 4.12 × 10 5 M −1 (Figure S8) by nonlinear fitting analysis of the titration curves. 30,31 It was found that APR has a detection limit of 0.15 nM for Hyp (Figure S9). The 1:1 stoichiometry of APR to Hyp was determined from Job's plot (Figure S10).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Synthesis of N-Boc-2-ethynylpyrrole (19). To a solution of N-Boc-2-bromopyrrole (18) 17 (2.07 g, 8.40 mmol, 1.00 equiv) in dry 1,4-dioxane (16.8 mL, 2.00 mL/mmol) were added TMS acetylene (1.54 mL, 10.9 mmol, 1.30 equiv), triethylamine (3.51 mL, 25.1 mmol, 3.00 equiv), Pd(PPh 3 ) 4 (96.0 mg, 84.0 μmol, 0.0100 equiv), and CuI (27.9 mg, 147 μmol, 0.0200 equiv) under argon. After being stirred at 80 °C for 24 h in a sealed tube, the reaction mixture was diluted with water.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…mp > 300 °C (lit. 17 > 300 °C); 1 H NMR (400 MHz, DMSO- d 6 ) δ: 11.7 (m, 2H), 8.05 (d, 1H, J = 8.4 Hz), 7.68 (m, 2H), 7.34 (m, 1H), 7.12 (m, 1H), 6.45 (d, 1H, J = 3.4 Hz), 6.24 (dd, 1H, J = 3.4, 2.4 Hz), 3.66 (s, 3H); 13 C NMR (100 MHz, DMSO- d 6 ) δ: 173.5, 167.7, 140.7, 139.6, 132.3, 124.8, 124.2, 123.6, 123.0, 122.5, 118.6, 113.5, 111.9, 109.8 51.9; FT-IR (neat): 3200, 2923, 1724, 1588, 1558, 1456, 1354, 1135 cm –1 ; HRMS [ESI]: calcd for C 15 H 12 N 2 O 3 Na [M + Na] + 291.0746; found 291.0736.…”
Section: Methodsmentioning
confidence: 99%